ICT in Professional Training of the Future Teachers in the Russian Federation, the Baltic Countries and in Japan - Osadchy, Vyacheslav (Pedagogical Discourse, 2011)
The article examines the experience of the Russian Federation, the Baltic countries and Japan on the issue of implementation of ICT in professional training of the future teachers, highlighting the positive aspects and achievements of these countries in informatization of professional pedagogical education.